ANALYSIS OF THE CONSUMERS PREFERENCES OF LIPSTICK PRODUCT AND ITS RELATIONSHIP WITH THE SEGMENTATION OF THE LIPSTICK PRODUCTS - Mohammad Wartaka (STIE Binaniaga, 2016)
The need for lipstick continues to increase along with the emergence of a new lipstick products both domestic and global brands to follow the needs of its consumers, the new product has a variety of functions other than just as a lip color, but also as a moisturizer / lip protection even as treatment. Adult lipstick is packed with advertisements and packaging are very interesting addition to the color choice of more and more. In determining the selection of lipstick products consumers often consider the combination of the main attributes and other factors that are trade-offs. This study aims to determine the attributes and combination of attributes among the most preferred by consumers for a segment of the age and the amount of income. Sources of data in this study were obtained from 138 respondents in the city of Bogor and its surroundings, conjoint analysis is used to determine the usefulness of each attribute and their relative weights as a tool to predict the preferences of a particular segment or as a whole. The results showed the order of importance weight according to the respondents is that the quality attributes (34.95%), the type of color (33.21%) and benefits (31.84%), while the combination of the most preferred products are: lipstick durable / waterproof, according to skin color, and functioning for moisturizing / protective lip. In the description also delivered conjoin analysis results for each age and income segments.Keywords: conjoint analysis, lipstick, part-worth utilities, post-hoc, trade-off, segmentation.